(untitled) (Journal of Academic Research, 2023)
Cervical cancer is one of the major public health concerns which represents the fourth most common cancer in women worldwide. Studies relating the incidence of cervical cancer with age are available in the literature, the present study was aimed at evaluating the relationship between age and cervical cancer type among women living with cervical cancer attending Misurata National Cancer Institute Hospital, Libya. The study population included 100 female patients with age range between 20 and >70 years. Data on benign squamous, malignant squamous, benign glandular and malignant glandular were retrieved. Variables in this study were analysed using SPSS version 21.0 statistical software. The relationship between the age and cancer type was performed using Chi-square test. Benign glandular was the most frequent cancer type recording 53 % followed by benign squamous and malignant glandular with each representing 19 % of the population. While, 9% of the population represent malignant squamous. Majority of the cervical cancer patients were within 40-49 age bracket while the least cancer incident was found among the patient between 20-29 years. No significant (p>0.05) association exist between the patients age and cancer type. The observation in this study supports the current trend where decline in the squamous cervical cancer incidence but increase in the glandular cervical cancer were reported. Also, the disease is commonest among young women at their productive age, thus cervical cancer is a major problem in the society.